Cover Image. (18th October 2020) - Banerjee, Sanchita; Ghosh, Prosenjit; Pramanik, Chirantan; Reddy B, Subba
Abstract : The cover image is based on the Research Article Fractionation of stable oxygen and clumped isotopes during acid digestion of calcite in the presence of an external direct current electric field by Sanchita Banerjee et al., https://doi.org/10.1002/rcm.8921 .